Malvidin Protects WI-38 Human Fibroblast Cells Against Stress-induced Premature Senescence - Seo, Hye Rin (J Cancer Prev, 2016)
BACKGROUND: Malvidin is one of the most abundant components in red wines and black rice. The effects of malvidin on aging and lifespan under oxidative stress have not been fully understood. This study focused on the anti-aging effect of malvidin on stress-induced premature senescence (SIPS) in WI-38 human lung-derived diploid fibroblasts. METHODS: In order to determine the viability of WI-38 cells, MTT assay was conducted, and malondialdehyde level was determined using thiobarbituric acid-reactive substance assay. Protein expression of inflammation-related factors was also evaluated by Western blot analysis. RESULTS: Acute and chronic oxidative stress via hydrogen peroxide (H(2)O(2)) treatment led to SIPS in WI-38 cells, which showed decreased cell viability, increased lipid peroxidation, and a shortened lifespan in comparison with non-H(2)O(2)-treated WI-38 cells. However, malvidin treatment significantly attenuated H(2)O(2)-induced oxidative stress by inhibiting lipid peroxidation and increasing cell viability. Furthermore, the lifespan of WI-38 cells was prolonged by malvidin treatment. In addition, malvidin downregulated the expression of oxidative stress-related proteins, including NF-κB, COX-2, and inducible nitric oxide synthase. Furthermore, protein expression levels of p53, p21, and Bax were also regulated by malvidin treatment in WI-38 cells undergoing SIPS. CONCLUSIONS: Malvidin may potentially inhibit the aging process by controlling oxidative stress.